Cognitive Behavioral Therapy Theories and Applications - Misciagna, Sandro (IntechOpen, 2020)
Cognitive behavioral therapy (CBT) is a modern type of short-term psychotherapy that integrates cognitive and behavioral theories. The CBT approach is effective in the treatment of a wide range of mental issues and conditions, such as generalized anxiety disorders, general or post-traumatic stress, panic attacks, depression, eating and sleep dysfunctions, obsessive-compulsive disorders, and substance dependence. CBT is also effective as an intervention for psychotic, personality, and bipolar disorders or to approach fatigue and chronic pain conditions especially if associated with distress. This book explains both theoretical and practical aspects of CBT, along with case examples, and contains useful tools and specific interventions for different psychological situations.